2022
DOI: 10.1002/cam4.5026
|View full text |Cite
|
Sign up to set email alerts
|

Mutational landscape and clinical outcome of pediatric acute myeloid leukemia with 11q23/KMT2A rearrangements

Abstract: Background Alterations of 11q23/KMT2A are the most prevalent cytogenetic abnormalities in acute myeloid leukemia (AML) and the prognostic significance of 11q23/KMT2A‐rearranged AML based on various translocation partners varies among different studies. However, few studies evaluated the molecular characteristics of 11q23/KMT2A‐rearranged pediatric AML. We aim to analyze the mutational landscape of 11q23/KMT2A‐rearranged AML and assess their prognostic value in outcomes. Methods The mutational landscape and cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…Of the 33 pAML subtypes, 11 were HSC-like (CD34 + ), eight GMP-like (AZU1 + , ELANE + ), eight monocyte-like (CD14 + , CD68 + , LYZ + ), three cDC-like (ITGAX + ), two mast-like (TPSAB1 + ) and one megakaryocyte-like (PPBP + ) (Fig 3D). Consistent with the diversity of KMT2A rearrangements 26 and "other" categories, 17 out of 21 patients formed patient-specific subtypes (>90% of cells in a subtype from one patient, Supplemental Figure 5). RUNX1, FLT3, and CBFB pAML subtypes overlapped between patients with only two out of sixteen patients forming patient-specific subtypes (Supplemental Figure 5).…”
Section: Analysis Of Matched Diagnosis End-of-induction and Relapse S...supporting
confidence: 59%
See 1 more Smart Citation
“…Of the 33 pAML subtypes, 11 were HSC-like (CD34 + ), eight GMP-like (AZU1 + , ELANE + ), eight monocyte-like (CD14 + , CD68 + , LYZ + ), three cDC-like (ITGAX + ), two mast-like (TPSAB1 + ) and one megakaryocyte-like (PPBP + ) (Fig 3D). Consistent with the diversity of KMT2A rearrangements 26 and "other" categories, 17 out of 21 patients formed patient-specific subtypes (>90% of cells in a subtype from one patient, Supplemental Figure 5). RUNX1, FLT3, and CBFB pAML subtypes overlapped between patients with only two out of sixteen patients forming patient-specific subtypes (Supplemental Figure 5).…”
Section: Analysis Of Matched Diagnosis End-of-induction and Relapse S...supporting
confidence: 59%
“…To examine the association of CD69 + IGLL1 + HSC-like pAML with proliferation, we compared its gene signature score with clinical BM blast percentage in the TARGET AML data and observed a significant positive correlation (R=0. 26,p<0.05,Fig 4E). Thus, DE and pathway analysis indicated that CD69 + IGLL1 + HSC-like pAML promotes poor outcomes via proliferative and anti-apoptotic gene expression.…”
Section: Analysis Of Matched Diagnosis End-of-induction and Relapse S...mentioning
confidence: 87%
“…Alterations of the KMT2A gene (also known as mixed lineage leukemia 1, MLL1 or MLL gene) located at 11q23.3 are found in both acute lymphoblastic leukemia (ALL) and AML, making up ∼10% of all leukemia cases in all age groups ( Winters and Bernt, 2017 ). KMT2A rearrangements ( KMT2A r) are one of the most common recurrent genetic aberrations found in 15%–25% of all newly diagnosed cases of pediatric AML ( Meyer et al, 2006 ; Meyer et al, 2009 ; Meyer et al, 2013 ; Meyer et al, 2018 ; Hoffmeister et al, 2021 ; Quessada et al, 2021 ; Meyer et al, 2023 ; Yuen et al, 2023 ). KMT2A r are particularly prevalent in infant AML, accounting for approximately 30% of children presenting below the age of 2 years.…”
Section: Molecular Characterization Of Pediatric Non-ds Amklmentioning
confidence: 99%
“…4 However, this did not seem to work well in pediatric AML. Yuen et al 5 demonstrated pediatric AML with KMT2A::MLLT1 had higher overall survival (OS) and lower relapse rates than KMT2A::MLLT3 . Balgobind et al 6 identified AML with KMT2A::MLLT11 had excellent outcome and failed to confirm favorable outcome of KMT2A::MLLT3 in pediatric AML.…”
mentioning
confidence: 99%